Association of resting heart rate and cardiovascular disease mortality in hypertensive and normotensive rural Chinese. Issue 5 (May 2017) - Zhang, Ming; Han, Chengyi; Wang, Chongjian; Wang, Jinjin; Li, Linlin; Zhang, Lu; Wang, Bingyuan; Ren, Yongcheng; Zhang, Hongyan; Yang, Xiangyu; Zhao, Yang; Zhou, Junmei; et al.
Abstract: Background: Studies have demonstrated an increased risk of cardiovascular disease (CVD)-associated death (CVD death) with increased resting heart rate (RHR); however, whether the association is consistent in rural Chinese with hypertension and normotension is unknown. We examined the association of RHR and CVD death by hypertension and normotension status in rural Chinese people. Methods: Baseline data for 20, 069 participants ≥18 years old were collected during July to August of 2007 and July to August of 2008; 17, 151 (85.5%) participants were followed up in July to August of 2013 and July to October of 2014. The association of RHR and CVD death was determined by Cox proportional hazards regression. Results: During a mean of 5.88 years (100, 889 person-years) of follow-up, we recorded 479 CVD deaths (309 in hypertensive participants). CVD death increased significantly with increasing RHR, beginning from 80 beats per minute (bpm), for hypertensive and normotensive participants. After adjusting for pulse pressure and other covariates, for hypertensive participants, risk of CVD death was increased with RHR 80–89 and ≥90 bpm. However, for normotensive participants, risk of CVD death was increased with only RHR ≥ 90 bpm. Conclusions: Risk of CVD death was associated with elevated RHR for both hypertensive and normotensive rural Chinese, and for hypertensive participants, even slightly elevated RHR was associated with CVD death.